Managing people with diabetes in the workplace: current difficulties and future opportunities in the light of new projects for chronic patients - Banchini, Gabriele; Santelia, Alfonso (La Medicina del Lavoro, 2020)
Diabetes is growing rapidly in Italy as well as in much of the world. In addition to representing a health emergency, it involves a great deal of difficulty for patients who require close diagnostic and therapeutic control. Greater difficulties still are observed in workers with diabetes: the pathology itself sometimes becomes the object of discrimination when employed, and often work commitments are an important obstacle to the correct carrying out of regular diagnostic procedures and checks for monitoring the disease. Starting from January 2020, as part of a project for the management of chronic patients by the Lombardy Region, a better organization of the diagnostic and therapeutic path of the diabetic subject is expected, managed in a more interactive way by the General Practitioner and the specialists, leading to a rationalization of costs, more accurate diagnostics and time savings for patients.